PATH ANALYSIS: CHARACTERISTICS AND APPLICATION IN SOCIOLOGICAL ANALYSIS (Annual of the Faculty of Philosophy in Skopje, 2012)
The main aim of this paper is to explain basic characteristics of the path analysis, and present some example of path analysis. Path analysis may have special usefulness in sociology. Path analyses focuses on the problem of interpretation and not intend to be a method of discovering causes. Path analysis is representing by path coefficient. There are differences between exogenous and endogenous variables. The main stapes in running path analysis are to define the variables, to represent in causal order, to formulate equation, and schem review of the path model. In the process of running variables all variables are regressed in once, and the order of the variables represent the causal order between them.
Keywords: PATH ANALYSIS; SOCIOLOGICAL RESEARCH